Use of Whole Exome Sequencing for the Identification of Ito‐Based Arrhythmia Mechanism and Therapy. Issue 5 (26th May 2015) - Sturm, Amy C.; Kline, Crystal F.; Glynn, Patric; Johnson, Benjamin L.; Curran, Jerry; Kilic, Ahmet; Higgins, Robert S. D.; Binkley, Philip F.; Janssen, Paul M. L.; Weiss, Raul; Raman, Subha V.; Fowler, Steven J.; et al.
Abstract : Background: Identified genetic variants are insufficient to explain all cases of inherited arrhythmia. We tested whether the integration of whole exome sequencing with well‐established clinical, translational, and basic science platforms could provide rapid and novel insight into human arrhythmia pathophysiology and disease treatment. Methods and Results: We report a proband with recurrent ventricular fibrillation, resistant to standard therapeutic interventions. Using whole‐exome sequencing, we identified a variant in a previously unidentified exon of the dipeptidyl aminopeptidase‐like protein‐6 ( DPP6 ) gene. This variant is the first identified coding mutation in DPP6 and augments cardiac repolarizing current ( I to ) causing pathological changes in I to and action potential morphology. We designed a therapeutic regimen incorporating dalfampridine to target I to . Dalfampridine, approved for multiple sclerosis, normalized the ECG and reduced arrhythmia burden in the proband by >90‐fold. This was combined with cilostazol to accelerate the heart rate to minimize the reverse‐rate dependence of augmented I to . Conclusions: We describe a novel arrhythmia mechanism and therapeutic approach to ameliorate the disease. Specifically, we identify the first coding variant of DPP6 in human ventricular fibrillation. These findings illustrate the power of genetic approaches for the elucidation and treatment of disease when carefully integrated with clinical and basic/translational research teams.